Numerical Analysis of Fractional Order Epidemic Model of Childhood Diseases. (3rd December 2017) - Haq, Fazal; Shahzad, Muhammad; Muhammad, Shakoor; Wahab, Hafiz Abdul; ur Rahman, Ghaus
Abstract : The fractional order Susceptible-Infected-Recovered (SIR) epidemic model of childhood disease is considered. Laplace–Adomian Decomposition Method is used to compute an approximate solution of the system of nonlinear fractional differential equations. We obtain the solutions of fractional differential equations in the form of infinite series. The series solution of the proposed model converges rapidly to its exact value. The obtained results are compared with the classical case.